Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd007689.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for polycystic ovarian syndrome

Abstract: Editorial group: Cochrane Gynaecology and Fertility Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 7, 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Due to the weakness of the methodological design, the overall quality of clinical trials concerning the effectiveness of acupuncture treatment for infertility in women with PCOS is relatively low [ 18 ]. Although an ongoing multicenter RCT is underway, more RCTs that are properly designed are needed before drawing conclusions concerning the use of acupuncture in the management of PCOS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the weakness of the methodological design, the overall quality of clinical trials concerning the effectiveness of acupuncture treatment for infertility in women with PCOS is relatively low [ 18 ]. Although an ongoing multicenter RCT is underway, more RCTs that are properly designed are needed before drawing conclusions concerning the use of acupuncture in the management of PCOS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is able to decrease abnormally high levels of circulating luteinizing hormone (LH), which affect the LH/follicle-stimulating hormone (FSH) ratio [ 14 , 16 ], and high levels of testosterone [ 17 ]. Additionally, the low associated adverse-events rate, a low risk of multiple pregnancies, and the low cost of acupuncture have been noted [ 18 ]. However, the methodological quality of these clinical trials varies, resulting in inconclusive statements on the effectiveness of acupuncture for PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Scrutiny of the Cochrane Database, purportedly the highest form of evidence and consisting of highquality, independent systematic reviews, only identified nine reviews which directly related to acupuncture and women's reproductive health (Yu et al, 2005;Zhang et al, 2010;Lim et al, 2011;Smith et al, 2011a;2011b;Zhu et al, 2011;Cheong et al, 2013;Dodin et al, 2013). These registered reviews assessed acupuncture for premenstrual syndrome (Yu et al, 2005), uterine fibroids (Zhang et al, 2010), polycystic ovary disease (Lim et al, 2011), dysmenorrhea (Smith et al, 2011a), endometriosis (Zhu et al, 2011), pain in labour (Smith et al, 2011b), induction of labour (Smith et al, 2013), menopausal hot flushes (Dodin et al, 2013), and assisted reproductive technology (Cheong et al, 2013). Of these nine reviews, three had no included studies (Yu et al, 2005;Zhang et al, 2010;Lim et al, 2011) and eight were carried out between 2010 and 2013.…”
Section: Evidence Base For Acupuncture and Female Reproductive Disordersmentioning
confidence: 99%
“…These registered reviews assessed acupuncture for premenstrual syndrome (Yu et al, 2005), uterine fibroids (Zhang et al, 2010), polycystic ovary disease (Lim et al, 2011), dysmenorrhea (Smith et al, 2011a), endometriosis (Zhu et al, 2011), pain in labour (Smith et al, 2011b), induction of labour (Smith et al, 2013), menopausal hot flushes (Dodin et al, 2013), and assisted reproductive technology (Cheong et al, 2013). Of these nine reviews, three had no included studies (Yu et al, 2005;Zhang et al, 2010;Lim et al, 2011) and eight were carried out between 2010 and 2013. The review by Smith et al (2011a) included ten trials (944 women) on acupuncture for dysmenorrhoea and provided some indication of reduction in period pain and similarly her review for management of pain during labour (13 trials, 1986 women) indicated that acupuncture may have a role in pain reduction and patients reported increased satisfaction and a reduction in the use of pharmacological management (Smith et al, 2013).…”
Section: Evidence Base For Acupuncture and Female Reproductive Disordersmentioning
confidence: 99%
“…44 Acupuncture is a safe, viable alternative. 44 In their review paper, Lim and Wong state that acupuncture may help to increase blood flow to the ovaries, reduce ovarian volume and the number of ovarian cysts, and control hyperglycaemia by increasing insulin sensitivity and decreasing blood glucose and insulin levels. Acupuncture's mode of action is by modulation of endogenous regulatory systems, including the sympathetic nervous system and the endocrine and the neuroendocrine systems.…”
Section: Research On Acupuncture and Pcosmentioning
confidence: 99%